EVALUATION OF IMPLEMENTATION OF HEALTH, SAFETY AND ENVIRONMENT (HSE) PROGRAM IN OIL AND GAS TRANSPORTATION COMPANY (IN THE HUMAN RESOURCE MANAGEMENT APPROACH) - Rakhmat Kabul, Eka; Madiistriyatno, Haries (Dinasti Publisher, 2021)
The focus of this research is to ensure that the implementation of the Health, Safety and Environment (HSE) program which runs as the goals and the objectives that have been set, the factors that lead to the success or failure of the program and the benefits derived from the implementation of the HSE program for employees and companies. This research is a qualitative research using the method of evaluation of the Context Input Process Product (CIPP) approach. Data taken using the guidelines interviews, questionnaires and observation studies and in the analysis of documents with descriptive methods through discussions and triangulation. All the activites of decision data is performed to all stakeholders components into aspects of evalution in this study include: Context Evaluation (C): The importance of goals and objectives in the implementation of the program; Input Evaluation (I): Strategies, procedures and activities of the program; Process Evaluation (P): Implemention process of the program; Product Evaluation (P): Outcomes and benefits of the program. The results showed that the implementation of HSE program is generally in accordance with its performance indicators but the success of the program has not been fully fulfilled because the program strategy is not directed and incomplete so that the implementation process is not quite as it should be because of the absence of adequate standard operation procedure. The recommendation of this research is that if the company wishes to continue the HSE program successfully, the company should review the vision, mission, goals and objectives of the program (Context), then fix the program strategy completely and purposefully (Input), completing the operation procedures, so that the implementation process in accordance with the standard operation procedure (Process)) that will further ensure the success of this HSE program (Product).